Development of complex exercise function test for Taekwondo Kyorugi athletes and establishment of criteria - Jeon, M.; Park, J. H.; Yoon, J.; Yun, H. J. (International Journal of Sports Science & Coaching, 2025)
This study aims to develop a complex exercise function test for Taekwondo athletes and establish a reference standard. To develop the tool, a group of 12 Taekwondo and evaluation experts were selected. Additionally, to establish the validity and criteria of the developed tool, 40 male college Taekwondo athletes were selected as research participants. To assess the content validity of the complex motor function test, the content validity ratio was computed for data processing. Additionally, validity based on the measured data was verified using an independent sample t-test, a well-known method for comparing different groups. Receiver Operating Characteristic (ROC) analysis was performed to establish reference points for each item for the developed Taekwondo complex motor function test. The optimal cut-point in ROC analysis was calculated using Area Under the Curve and You den's J index. Furthermore, accuracy, sensitivity, and specificity were calculated to verify the cut-point's validity. All statistical analyses were performed using Excel 2016 and IBM SPSS 25.0. The significance level was set to .05. Four items were developed as preliminary items for the Taekwondo complex motor function test. As a result of validating them, three items were finally developed: T1, T3, and T Plus. In addition, as reference points for the developed Taekwondo complex motor function test, T1 was set to 23.1 s, T3 to 55.3 s, and T Plus to 35.7 s.